Enterovirus 71 Induces INF2 Cleavage via Activated Caspase-2 in Infected RD Cells - Wang, Bei; Zhang, Chongyang; Yu, Congci; Zhu, Yue; Tang, Qing; Huang, He; Zhao, Zhendong (Frontiers in Microbiology, 2021)
Enterovirus 71 (EV71) is the major causative pathogen of hand, foot, and mouth disease. The lack of understanding of its viral pathogenesis precludes the development of drugs against this virus and the control of EV71 infection. Our previous studies have demonstrated that both mitochondria and endoplasmic reticulum (ER) were changed significantly in EV71 infected cells, but the mechanism is still unclear. In this study, we investigate the expression of INF2, a key regulator factor in ER-Mitochondria communication and mitochondrial fission in infected cells. We found that INF2 is cleaved in EV71 infected RD cells. The INF2 cleavage occurred at Aspartic 1051 of INF2 and is mediated by activated caspases, predominantly by activated caspase-2. The distribution of INF2 and caspase-2 changed significantly in infected cells, and we speculate that caspase-2-mediated INF2 cleavage participates in viral replication organelle (ROs) formation and is a positive feedback regulatory mechanism of EV71 caused mitochondrial disorders.